Fishing nets and video creation: diabetic nephropathy education on screen - Ângela Paveglio Teixeira Farias; Morgana Vielmo Cáceres; Manoela Michel Kohl; Márcio Mossmann; Eduardo Dallazen; Isadora Rosy Pontalti (2021)
Abstract: Introduction: Noncommunicable Chronic Diseases (NCDs), such as Diabetes and Hypertension are responsible for 2/3 of deaths in the world, with Diabetic Nephropathy (DN) representing the most important cause of chronic kidney disease. Health Literacy (HL) is one of the social determinants of health. To guide and expand the knowledge of patients and teams involved in the care of people with NCDs, and for a better approach to chronic complications of Diabetes and Hypertension, the development of learning objects (LO) was proposed. Experience Report: this study involved the construction of an educational video by a group of five students during the academic program of undergraduate Medical School in 2019. They proposed a guiding question in relation to DN from a theoretical material. The chosen question was: “What is the level of understanding of patients with diabetic nephropathy in relation to their own disease?”. They developed a questionnaire on diabetes and hypertension and their complications, which was answered by patients with diabetes who were treated at the specialized outpatient clinic, aiming to answer the proposed problem. They drew a synthesis from the analysis of the responses, of the possible gaps in relation to the understanding of the diseases. Then, a script was created with the description of these gaps with the medical explanation and an analogy was made with fishing nets for the video production, containing narratives, texts, audios and images. Finally, the video was presented to teachers and students in the classroom. Discussion: The characterization of the video as an LO implies constructing it as an educational component, self-sufficient, reusable and with the possibility of combining it with other LOs as new educational tools. Conclusion: The educational material was characterized as an LO. It allows pointing out aspects of the progression of DN and recommended medical orientations for the disease. It establishes a tool for group discussions and isolated actions based on succinct and evidence-based medical information. The video validation is undergoing validation for use in health services.